2018
DOI: 10.1002/uog.19000
|View full text |Cite
|
Sign up to set email alerts
|

Does freeze‐all policy affect IVF outcome in poor ovarian responders?

Abstract: The freeze-all strategy, compared with fresh ET, had no impact on IVF outcomes in POR patients as defined according to the Bologna criteria. Multicenter studies including large numbers of patients should be carried out to confirm the results of this study and reach conclusions about the potential benefits of the freeze-all policy for poor responders. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
(98 reference statements)
1
15
0
1
Order By: Relevance
“…In 2018, Roque et al reported a meta-analysis and indicated that the e-FET strategy resulted in a significantly higher LBR in hyper-responders (RR = 1.16; 95% CI: 1.05-1.28). However, the CLBR was not significantly different in the overall population (RR = 1.04; 95% CI: 0.97-1.11) [39]. Notably, the meta-analyses combined studies that randomized patients after the oocyte yield was known and excluded patients with an inadequate or excessive ovarian response.…”
Section: Plos Onementioning
confidence: 98%
See 2 more Smart Citations
“…In 2018, Roque et al reported a meta-analysis and indicated that the e-FET strategy resulted in a significantly higher LBR in hyper-responders (RR = 1.16; 95% CI: 1.05-1.28). However, the CLBR was not significantly different in the overall population (RR = 1.04; 95% CI: 0.97-1.11) [39]. Notably, the meta-analyses combined studies that randomized patients after the oocyte yield was known and excluded patients with an inadequate or excessive ovarian response.…”
Section: Plos Onementioning
confidence: 98%
“…Although some observational studies have compared fresh ET and freeze-all strategies, no RCTs have evaluated the effects of the e-FET strategy on poor responders [39][40][41][42]. Three of these observational studies including cleavage-stage ETs did not report any benefit of using the freeze-all strategy [39][40][41].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…However, due to advances in the field of cryobiology [7,8], this is no longer necessary. Ovarian stimulation can conclude with elective freezing of oocytes or embryos, with similar results to those of a fresh embryo transfer [9] even in patients with poor response [10]. In fact, one of the proposed strategies in patients with poor response is the accumulation of oocytes for subsequent fertilization [11].…”
Section: Introductionmentioning
confidence: 95%
“…The switch from slow programmed frozen methods to current vitrification methods has greatly improved ART efficiency (Zhu et al, ). Thus, freezing embryos has become a routine practice for ART units, and some units have recently even started to use the “freeze‐all” strategy for certain patients (Bhattacharya, ; Roque, Valle, Sampaio, & Geber, ). Although these techniques are currently an indispensable component of ART, increase in apoptotic gene expression and DNA fragmentation (Park et al, ) and lower hatching rates of mouse blastocysts (Yao et al, ) have been reported to result from cryopreservation.…”
Section: Introductionmentioning
confidence: 99%